Glass Ceiling Analysis in the Bureaucracy Within the Patriarchy and Religious Society - dan Syafatania, Fatimah Umar, Musta’in Mashud, Suryanto, (Opción, 2019)
This research was conducted to find out the way women employees could break through the glass ceiling to get access onto the top positions in the bureaucracy of Sumenep Regency of Madura Island, with patriarchy and religious cultures that usually limit woman’s space in public sphere. This research is based on phenomenological approach. It is found that 9 women been able to occupy the top positions, while the other 2 remained at the bottom line as staffs without any career advancement. In conclusion, the actual glass ceilings were inside themselves, such as low motivation, low level of education and competence.